An enquiry concerning human understanding - Hume, David; Millican, Peter (New Delhi: Oxford university Press, 2008)
"Over a series of elegantly written, engaging essays, the Enquiry examines the experiential and psychological sources of meaning and knowledge, the foundations of reasoning about matters that lie beyond the scope of our sensory experience and memory, the nature of belief, and the limitations of our knowledge. The positions Hume takes on these topics have been described as paradigmatically empiricist, sceptical, and naturalist and have been widelyinfluential and even more widely decried. The introduction to this eiditon discusses the Enquiry's origin, evolution, and critical reception, while appendices provide examples of contemporary responses to Hume"--Page 4 of cover.
Includes bibliographical references and index.
Keywords: KNOWLEDGE THEORY